Speculative fiction, criticality, and futurity: an introduction. Issue 3 (3rd July 2021) - LeMaster, Lore/tta; Johnson, Amber
ABSTRACT: This short essay introduces the reader to the special issue, Speculative Fiction, Criticality, Futurity, featuring original short speculative fiction, flash fiction, graphic novels, and visual art–each of which critically imagines liberatory futurities. Each submission contributes to a different component of futuristic world-making. Some of the pieces tend to the messy fight against neo-fascism by speaking to the various tactics to dismantle supremacy. Other pieces situate their protagonists in post-apocalyptic worlds where the fight for liberation has ended with new equitable systems. Other pieces revise historical moments in an effort to reimagine what our current lives could be like without injustices chaperoning our existence. Regardless of the approach, each piece pushes us to imagine the fight and future ahead.